2021
DOI: 10.1055/s-0041-1724121
|View full text |Cite
|
Sign up to set email alerts
|

Injury Patterns in Pediatric Facial Fractures Unique to an Urban Environment

Abstract: This study aimed to define better the clinical presentation, fracture patterns, and features predictive of associated injuries and need for surgery in pediatric facial trauma patients in an urban setting. Charts of patients 18 years or younger with International Classification of Disease 9th and 10th revision (ICD-9/ICD-10) codes specific for facial fractures (excluding isolated nasal fractures) at NY-Presbyterian/Weill Cornell Medical Center between 2008 and 2017 were retrospectively reviewed. Of 204 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…Characteristics of 58 studies 7,9,11,21–75 included in the meta‐analysis are shown in Table 1. The studies included a case range of 37–183,336 cases.…”
Section: Resultsmentioning
confidence: 99%
“…Characteristics of 58 studies 7,9,11,21–75 included in the meta‐analysis are shown in Table 1. The studies included a case range of 37–183,336 cases.…”
Section: Resultsmentioning
confidence: 99%
“…Several prior studies have used ICD codes to define cohorts and outcomes in ophthalmic infections and trauma. 31 , 32 , 33 , 34 , 35 Ophthalmic researchers should be aware of the implications of the lack of granularity in some ICD codes and consider that when determining study methodologies. Several EHR systems include mapping to SNOMED-CT, 36 which provides significantly higher proportions of equal representation of ophthalmic clinical concepts and may be more preferable when planning research studies.…”
Section: Discussionmentioning
confidence: 99%
“…Presentation upon arrival to the emergency department varies depending on the mechanisms of the head trauma. Blunt injuries might mean certain patients require wound management or specialist consultations from the otolaryngological or ophthalmological fields [27].…”
Section: Two Medium-risk Factorsmentioning
confidence: 99%